Clarias batrachus linnaeus, 1758 (siluriformes, clariidae): new records of threatened catfish from Bawean Island, Indonesia - Tamam, Muhammad Badrut; Ramadani, Aisyah Hadi; Valen, Fitri Sil (Generasi Biologi Indonesia, 2021)
Clarias batrachus Linnaeus, 1758 is one of catfish in Indonesia. The spread of Clarias batrachus in Indonesia have generally in mainland of Sumatra, Borneo and Java. In 2019 we report for the first time the presence of C. batrachus on Bawean, a small, isolated island, conservation area in the middle of Java Sea. A description of morphological characters of a specimen are provided. Presence of C. batrachus on Bawean Island caused by the geographical reason and human introduction factors.